Prognostic significance of baseline peripheral absolute neutrophil, monocyte and serum β2‐microglobulin level in patients with diffuse large b‐cell lymphoma: a new prognostic model. (22nd July 2016) - Chen, Yiming; Neelapu, Sattva; Feng, Lei; Bi, Weiqi; Yang, Tian‐Hui; Wang, Michael; Fanale, Michelle A.; Westin, Jason R.; Hagemeister, Fredrick B.; Fayad, Luis E.; Romaguera, Jorge E.; Samaniego, Felipe; et al.
Summary: There are limited reports that baseline peripheral absolute neutrophil count (ANC), absolute monocyte count (AMC), absolute lymphocyte count (ALC) and serum β2‐microglobulin level independently predict survival in patients with diffuse large B‐cell lymphoma (DLBCL). To confirm these findings, we analysed these parameters together with components of the International Prognostic Index (IPI) in patients with newly‐diagnosed DLBCL. We evaluated baseline clinical features for their ability to predict survival in 817 newly diagnosed, previously untreated patients with DLBCL who received frontline treatments between October 2001 and December 2011. The median age at diagnosis was 58 years. Multivariate analysis identified elevated baseline ANC ( P = 0·036), AMC ( P = 0·028) and serum β2‐microglobulin level ( P < 0·001), poor performance status ( P < 0·001) and high number of extranodal disease sites ( P = 0·0497) as independent unfavourable predictors of OS; serum β2‐microglobulin level was the strongest predictor of survival outcomes among all the parameters. High baseline serum β2‐microglobulin, ANC and AMC levels are independent prognostic factors for short overall survival in patients with newly diagnosed DLBCL. Our new model, based on the above five parameters, better stratifies patients into various risk categories than the IPI for newly diagnosed DLBCL.